Co-designing a method to assess agroecological transitions: results of a case study in Senegal - Darmaun, Maryline; Hossard, Laure; de Tourdonnet, Stéphane; Chotte, Jean-Luc; Lairez, Juliette; Scopel, Eric; Faye, Ndeye Fatou; Chapuis-Lardy, Lydie; Ndienor, Moussa; Cissé, Mame Farma Ndiaye; Chevallier, Tiphaine (Italian Journal of Agronomy, 2023)
Assessing the conditions and performance of agroecological transitions in different contexts is key to supporting these transitions. However, assessing agroecological transitions presents methodological challenges, including: 1) being adaptable to local conditions, 2) consideration of social interactions among stakeholders involved in transitions, 3) clarifying the concept of agroecology, 4) consideration of the temporal dynamics of the transitions to better understand barriers and levers in their development, and 5) using a participatory bottom-up approach. The objective of this research was to design a method that provided evidence on 1) the barriers and levers in the development of agroecological transitions, and 2) their performance related to four dimensions: techno-economic issues, agroecosystem health, quality of life and resilience. To design, test and adapt such a method, while also involving end-users, we adopted a co-design approach based on prototyping. The co-design approach unfolded in nine stages alternating research work and co-design with end-users. The prototype was built on the approaches of existing published methods covering the five challenges for assessing agroecological transitions. It consisted of a four chronological step assessment method. The first three steps consisted of framing the assessment, with the final step a multidimensional performance assessment, using an initial set of 73 indicators to cover the four dimensions. The prototype was then tested and adapted in the village of Sare Boubou, Senegal, which is going through an agroecological transition supported by a non-governmental organization. Changes during the testing and adaptation phase affected three steps of the prototype and allowed the initial prototype to adapt to the case study’s specificities, related to its scale and context. Context-related changes particularly affected the performance assessment, with a total of 31 indicators changed. The analysis of barriers and levers revealed that the transition began 29 years ago, achieved a fair level of advancement and yet was still ongoing. Results revealed heterogeneity between the nine households of the village in terms of: uptake of agroecological practices, household resources, diversification of activities, coverage of food needs through production and level of sales. This heterogeneity explained the large variability in household multidimensional performances across all dimensions. Large disparities were also noticeable at the individual level between men, women and young men in the village regarding the level of education, empowerment and participation in knowledge sharing networks. Despite a method seen as time-consuming and data intensive, end-user validation acknowledged the comprehensiveness of the method and its usefulness for steering and managing agroecological transitions, making it possible to identify levers for action at different scales.